A produção de sentidos para o brincar em um contexto de educação formal e sua repercussão na aquisição da linguagem escrita - Azevedo, Mônica Maria de (2007)
This research investigates the production of meaningful playing in a social institucional context of formal education. The focus of this research is in such a way to make a quarrel on the directions attributed when playing for the school, through the form as it organizes and circumscribes this activity in its spaces, how much for the teacher through its of pedagogical practical classroom, in a specife context of formal education. This quarrel was supported by the conceptual definition that Vygotsky carries through on the processes of interaction and mediation, on the relation sensible/meant and the importance of the context in its constitution, enriched for the contributions of Wertsch on the importance of the social institucional contexts and the contributions of Baquero in practical relation to the mediation of the pedagogical ones. The used instruments had been:observation of pedagogical practices in a literacy classroom and places outside the classroom where children can play, as well as interviews with the principal and the teacher. The analysis of the interviews was done through the Analysis of Content, from which were established subcategories of analysis. The crossing of the data analyses and observations show the different meanings attributed to playing in this specific context of formal education the same relate the trespass, danger and regulation of content, reverberating in the development of the symbolic function that characterizes the process of acquisition of the written language.